Rapport Management Framework in Classroom Interaction: A Socio-pragmatic Analysis of Teachers' Utterances - Syting, Christian Jay O. (Journal Corner of Education, Linguistics, and Literature, 2025)
This qualitative descriptive study employing socio-pragmatic analysis aimed to analyze teachers' utterances using Spencer-Oatey's Rapport Management Framework, essential for improving teacher-student relationships and enhancing classroom dynamics. A 6-hour classroom observation and interview with 10 teachers were conducted to collect the data. The framework includes face and social rights. In terms of face, it involved the quality face, which comprised well-being concern, dialogue encouragement, openness to diverse perspectives, respect for diverse opinions, feedback and encouragement, fairness and humility; social identity face, which comprised of behavioral guidance, authority establishment, group engagement, effort encouragement, participation seeking, attention direction, guidance of understanding, correctness assurance, and support reinforcement; and relational face, which comprised of managing classroom dynamics, gentle correction, commitment to personalized support, promotion of mutual support, validation and clarification strategy. On the other hand, sociality rights involved association and equity rights: the latter consisted of the principles of involvement, empathy, and respect, while the former consisted of cost-benefit consideration, fairness and reciprocity, and autonomy-control. The results imply that both face and sociality rights can be sources of offense. Face is important for maintaining students' personal/relational/social value, while sociality rights help ensure fairness, consideration and behavioral appropriateness. These elements are important for teachers when interacting with students because they promote respectful communication and strengthen teacher-student relationships. The inclusion of these concepts in the curriculum helps create a positive and inclusive classroom environment.